Blockade of Endothelial-Mesenchymal Transition by a Smad3 Inhibitor Delays the Early Development of Streptozotocin-Induced Diabetic Nephropathy - Li, Jinhua (American Diabetes Association, 2010)
OBJECTIVE: A multicenter, controlled trial showed that early blockade of the renin-angiotensin system in patients with type 1 diabetes and normoalbuminuria did not retard the progression of nephropathy, suggesting that other mechanism(s) are involved in the pathogenesis of early diabetic nephropathy (diabetic nephropathy). We have previously demonstrated that endothelial-mesenchymal-transition (EndoMT) contributes to the early development of renal interstitial fibrosis independently of microalbuminuria in mice with streptozotocin (STZ)-induced diabetes. In the present study, we hypothesized that blocking EndoMT reduces the early development of diabetic nephropathy. RESEARCH DESIGN AND METHODS: EndoMT was induced in a mouse pancreatic microvascular endothelial cell line (MMEC) in the presence of advanced glycation end products (AGEs) and in the endothelial lineage–traceble mouse line Tie2-Cre;Loxp-EGFP by administration of AGEs, with nonglycated mouse albumin serving as a control. Phosphorylated Smad3 was detected by immunoprecipitation/Western blotting and confocal microscopy. Blocking studies using receptor for AGE siRNA and a specific inhibitor of Smad3 (SIS3) were performed in MMECs and in STZ-induced diabetic nephropathy in Tie2-Cre;Loxp-EGFP mice. RESULTS: Confocal microscopy and real-time PCR demonstrated that AGEs induced EndoMT in MMECs and in Tie2-Cre;Loxp-EGFP mice. Immunoprecipitation/Western blotting showed that Smad3 was activated by AGEs but was inhibited by SIS3 in MMECs and in STZ-induced diabetic nephropathy. Confocal microscopy and real-time PCR further demonstrated that SIS3 abrogated EndoMT, reduced renal fibrosis, and retarded progression of nephropathy. CONCLUSIONS: EndoMT is a novel pathway leading to early development of diabetic nephropathy. Blockade of EndoMT by SIS3 may provide a new strategy to retard the progression of diabetic nephropathy and other diabetes complications.